A flexible skin material with switchable wettability for trans-medium vehicles - Jianqiao Luo; Zhongjun Cheng; Ning Yu; Yunbo Tian; Junhui Meng (International Journal of Smart and Nano Materials)
Trans-medium vehicles can achieve both load reduction and trajectory stabilization through the adaptive adjustment of head configurations and surface wettabilities, necessitating a flexible skin material with switchable wettability. However, conventional deformable materials often exhibit insufficient load-bearing capacity under impact loads, and their deformation can cause the failure or delamination of surface coatings, leading to undesirable changes in wettability. In this paper, shape memory polymer (SMP) is utilized as the substrate of the flexible skin material, and is reinforced with S-shaped shape memory alloy (SMA) wires to overcome inherent limitations in strength and stiffness. A smart, responsive coating with switchable wettability is constructed by spraying perfluorooctanoic acid (PFOA)-grafted SiO2 nanoparticles onto the SMP substrate, thereby mitigating the adverse effects of substrate deformation on the performance of surface coatings. Experimental results demonstrate that SMA reinforcement enhances the material’s elastic modulus and ultimate strength to 2.32 GPa and 31.6 MPa, respectively, at room temperature, and the material can achieve a maximum deformation rate of 15% at 80 ℃. The PFOA-grafted SiO2 coating enables reversible wettability transitions between superhydrophobic and superhydrophilic states, even after the substrate undergoes repeated cyclic deformation. This paper provides a valuable reference for the development of next-generation trans-medium vehicles.